The impact of medical insurance and old-age security on the utilization of medical services by the older population with disabilities - Xiaomeng Tao; Yanbing Zeng; Weiping Jiao (BMC Health Services Research, 2024)
Abstract Objective In this study, the impact of medical insurance and old-age security on the use of medical services by the older population with disabilities is analyzed. A reference for decision makers is provided to improve medical and old-age security policies and enhance the use of medical services by the older population. Methods Data were drawn from 3,737 older people with disabilities aged 65 years or above from the 2018 China Longitudinal Healthy Longevity Survey. A two-part model based on social ecological theory was used for both analysis and group prediction. Results In terms of the use of outpatient medical services, old-age pension significantly increased the probability of outpatient visits for this population group (P < 0.05). Urban employee/resident medical insurance, the new rural cooperative medical insurance, and retirement pension significantly affected medical expenses. In terms of the use of inpatient medical services, the new rural cooperative medical insurance and retirement pension significantly influenced the choice of inpatient medical services; retirement pension increased inpatient medical expenditure (p < 0.01). The expected average probability of hospitalization, unconditional expected cost, and conditional expected cost for the older population with disabilities were 49.5%, RMB 6629.31, and RMB 3281.51, respectively. Both conditional and unconditional expected costs were significantly higher for older people with disabilities with the following attributes: male, married, no less than three chronic conditions, and unassisted daily care; costs were lower for older people with disabilities who are female, not married, had less than three chronic conditions, and had a spouse, child, or other caregiver. Conclusion Medical insurance and old-age security can significantly promote the utilization of medical services by the older population with disabilities. It is therefore recommended to focus on strengthening the support and health management of these people who are unattended to improve the effective use of health services and better meet their needs.